2011
DOI: 10.1002/pbc.23194
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization and risk of childhood leukemia in Greece and Sweden

Abstract: IVF seems to be associated with increased risk of early onset ALL in the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
3
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 45 publications
4
51
3
6
Order By: Relevance
“…The results suggest that IVF is associated with increased risk of early onset acute lymphoblastic leukemia (ALL) in the offspring. Increased risk of leukemia was observed with 3.8 years earlier in IVF offspring than in the control (OR 2.21, 95% CI 1.27-3.85) (Petridou et al, 2012). Meanwhile, a moderately increased risk of cancer in IVF children (RR 1.42, 95% CI 1.09-1.87) has also been observed by Källén B. et al (2010a) through a follow-up study of 26 692 children who were born after ART between 1982 and2005. In brief, the evidence of cancer risk in children after ART is still very limited.…”
Section: Risk For Cancermentioning
confidence: 92%
“…The results suggest that IVF is associated with increased risk of early onset acute lymphoblastic leukemia (ALL) in the offspring. Increased risk of leukemia was observed with 3.8 years earlier in IVF offspring than in the control (OR 2.21, 95% CI 1.27-3.85) (Petridou et al, 2012). Meanwhile, a moderately increased risk of cancer in IVF children (RR 1.42, 95% CI 1.09-1.87) has also been observed by Källén B. et al (2010a) through a follow-up study of 26 692 children who were born after ART between 1982 and2005. In brief, the evidence of cancer risk in children after ART is still very limited.…”
Section: Risk For Cancermentioning
confidence: 92%
“…Thus, fertility drugs, assisted reproductive technologies (ART), which involve further manipulation of the gametes, infertility itself through ovulation disorders, functional abnormalities and hormonal imbalances may be associated with CL risk. A few previous published studies reported positive associations between CL, infertility [8,9] and some fertility treatments [8,[10][11][12], albeit with inconsistency regarding the type of treatment. Petridou et al [12], reported a twofold increase in risk with in vitro fertilization (IVF), but the finding was not replicated by Rudant et al [8] in the ESCALE study or in a recent UK cohort study [13].…”
Section: Introductionmentioning
confidence: 93%
“…A few previous published studies reported positive associations between CL, infertility [8,9] and some fertility treatments [8,[10][11][12], albeit with inconsistency regarding the type of treatment. Petridou et al [12], reported a twofold increase in risk with in vitro fertilization (IVF), but the finding was not replicated by Rudant et al [8] in the ESCALE study or in a recent UK cohort study [13]. On the contrary, the ESCALE study showed an association between CL and ovulation induction without IVF or artificial insemination (AI), suggesting a role of drugs other than gonadotropins.…”
Section: Introductionmentioning
confidence: 93%
“…(An increased incidence in early childhood leukemias for products of in vitro fertilization has been reported. 1 ) The spleen was palpable down to the pelvis and 3 cm across the midline. Results of the complete blood count and differential showed white blood cell (WBC) count 335 ϫ 10 3 /L with 17% neutrophils, 18% bands, 6% eosinophils, 5% basophils, 19% metamyelocytes, 8% myelocytes, 1% promyelocytes, 6% blasts, 5% monocytes, 14% lymphocytes, and 4% nucleated red blood cells, hemoglobin 6.2 g/dL, and platelets 713 ϫ 10 3 /L.…”
Section: Introductionmentioning
confidence: 99%